Engineering of the High-Power Laser-Induced Synthesis of Ni-Based Metal-Organic Framework: Investigation of its Optical Properties, Computational Methodology, Electrocatalytic Performances, and Glucose-Sensing Ability - Mutlu, Saliha; Ortac, Bulend; Karatutlu, Ali; Gorkan, Taylan; Durgun, Engin; Soyler, Dilek; Soylemez, Saniye; Arsu, Nergis; Yilmaz, Sevil Savaskan (WILEY-V C H VERLAG GMBH, 2025)
Metal-organic frameworks (MOFs) are porous materials with numerous chemical and structural possibilities. Due to their ease of modification, well-organized structure, and diverse guest molecule chemistry, MOFs are ideal platforms for uncovering improved functional material design characteristics. Quantitative analysis of glucose is crucial, especially in some food products, for quality control as well as evaluation of the glucose levels helps diagnose and treat diabetes. Recent glucose sensing devices have relied heavily on MOFs and other nanomaterials to enable user-friendly and safe non-invasive sensing methods. Nevertheless, the conventional synthesis methods involve multi-day reactions, cooling, and depressurization processes. This study demonstrates the unprecedented high-power laser-induced rapid synthesis (LIRS) of Ni-based MOF nanospheres with interconnected nano-rods and noncentrosymmetric primitive triclinic crystalline structure, highlighting their multifunctional usage in sensing and gas sorption applications. Ab initio simulations show excellent agreement with the experimental physical and gas sorption properties. Furthermore, the Ni-MOF-based biosensor accurately measures glucose real-life beverage samples, yielding promising glucose detection biosensor results with a low limit of the detection (LOD) of 13.96 mu M and high sensitivity of 120.606 mu A mM-1 cm-2. The unprecedented high-power laser-induced rapid synthesis (LIRS) of Ni-based MOF nanospheres with interconnected nano-rods and noncentrosymmetric primitive triclinic crystalline structure is demonstrated, and due to the large amount of electrochemical active sites for the oxidation of glucose, the glucose levels within the real-life beverages are applied to detect with the LOD (13.96 mu M) and high sensitivity (120.606 mu A mM-1 cm-2). image
Keywords: ab initio simulations; density functional theory (DFT); glucose biosensor; laser technique; metal-organic framework; rietveld analysis; SELECTIVE NONENZYMATIC GLUCOSE; CARBON NITRIDE FILMS; CATALYST ELECTRODE; GOLD-NANOPARTICLE; MOF; ENZYME; NANOSHEETS; NANOWIRES; NICKEL; GAS; Materials Science